2021
DOI: 10.1097/aud.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Language Skills in Children With Bilateral Hearing Aids or Bilateral Cochlear Implants at the Age of Three Years

Abstract: Objectives: Early hearing aid (HA) fitting and cochlear implants (CIs) aim to reduce the effects of hearing loss (HL) on spoken language development. The goals of this study were (1) to examine spoken language skills of children with bilateral HAs and children with bilateral CIs; (2) to compare their language skills to the age-norms of peers with normal hearing (NH); and (3) to investigate factors associated with spoken language outcomes. Design: Spoken language results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…First, we identified language scores that were below scores of age- and SES-matched CTH at clinically significant levels 1.5 SDs below mean of the CTH. Various values have been used as a criterion for disordered or delayed communication in the research on language disorders and on children who are deaf and hard of hearing, ranging from >1 to 2 SD below the normative mean of a given test (Tomblin et al 1996; Ramus et al 2013; Bishop 2014; Reilly et al 2014; Geers et al 2016; Norbury et al 2016; Hansson et al 2018; Välimaa et al 2022). We chose to set 1.5 SD as the threshold for language delay in this analysis to capture the median of this range of definitions.…”
Section: Methodsmentioning
confidence: 99%
“…First, we identified language scores that were below scores of age- and SES-matched CTH at clinically significant levels 1.5 SDs below mean of the CTH. Various values have been used as a criterion for disordered or delayed communication in the research on language disorders and on children who are deaf and hard of hearing, ranging from >1 to 2 SD below the normative mean of a given test (Tomblin et al 1996; Ramus et al 2013; Bishop 2014; Reilly et al 2014; Geers et al 2016; Norbury et al 2016; Hansson et al 2018; Välimaa et al 2022). We chose to set 1.5 SD as the threshold for language delay in this analysis to capture the median of this range of definitions.…”
Section: Methodsmentioning
confidence: 99%
“…Nicholas et al also analyzed vocabulary, expressive and receptive language at 4.5 years of age and showed that children implanted between 6 and 11 months ( n = 27) achieved higher scores on all measures compared to those implanted between 12 and 18 months ( n = 42) [ 39 ]. Numerous studies demonstrated similar results regarding improved language trajectories among infants implanted <12 months [ 27 , 38 , 40 , 41 , 42 , 43 ]. However, Leigh et al showed no significant difference in the rate of receptive language growth between children implanted <12 months compared to those implanted between 13 and 24 months [ 44 ].…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, even after the improvements that early intervention can produce, language development still supposes a challenge for deaf or hard of hearing (DHH) children (Välimaa et al, 2022). Some authors mention the existence of developmental sensitive periods, related to environmental experiences, although it is difficult to determine the exact time where the development of a certain function is at its pike (Gabard-Durnam & McLaughlin, 2020;Gariépy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%